PENGARUH VARIASI PRODUK INDOMIE RASA RENDANG DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Muhammad Vito Prasetiyo; Nabila Arisanti; Irma Elvira Rizki; Naurah Azzahra Qurratu’ain; Annisa Safitri; Andira Putri Balkis; Rasyad Fiqry Caturitama; Kurniawati Mulyanti (Cahaya Ilmu Bangsa, 2024)
Indomie has low sales in 2024, down around 1.2% from 2023 and the quality of Indomie products still has high MSG content so consumers are worried about using Indomie products. The problem with Indomie product variations is that there is a gap between the various flavor variations, but the rendang flavored Indomie product variations have the lowest sales. This research method uses quantitative methods using SPSS Version 25. The results of this research are that the quality and product variations Indomie rendang flavor has a positive and significant influence on purchasing decisions. Indomie companies should improve the quality of the ingredients used to ensure health for consumers. And the Indomie company should evaluate several flavor variations that consumers are less interested in, such as the rendang flavored Indomie product variations. Because this will help increase sales of Indomie products with other flavor variations Keywords : kualitas, variasi produk, Keputusan pembelian